Intraoperative Scintigraphy Using a Large Field-of-View Portable Gamma Camera for Primary Hyperparathyroidism: Initial Experience. (6th January 2015) - Hall, Nathan C.; Plews, Robert L.; Agrawal, Amit; Povoski, Stephen P.; Wright, Chadwick L.; Zhang, Jun; Martin, Edward W.; Phay, John
Abstract : Background. We investigated a novel technique, intraoperative 99 m Tc-Sestamibi (MIBI) imaging (neck and excised specimen (ES)), using a large field-of-view portable gamma camera (LFOVGC), for expediting confirmation of MIBI-avid parathyroid adenoma removal. Methods. Twenty patients with MIBI-avid parathyroid adenomas were preoperatively administered MIBI and intraoperatively imaged prior to incision (neck) and immediately following resection (neck and/or ES). Preoperative and intraoperative serum parathyroid hormone monitoring (IOPTH) and pathology (path) were also performed. Results. MIBI neck activity was absent and specimen activity was present in 13/20 with imaging after initial ES removal. In the remaining 7/20 cases, residual neck activity and/or absent ES activity prompted excision of additional tissue, ultimately leading to complete hyperfunctioning tissue excision. Postexcision LFOVGC ES imaging confirmed parathyroid adenoma resection 100% when postresection imaging qualitatively had activity (ES) and/or no activity (neck). The mean ± SEM time saving using intraoperative LFOVGC data to confirm resection versus first IOPTH or path result would have been 22.0 ± 2 minutes (specimen imaging) and 26.0 ± 3 minutes (neck imaging). Conclusion. Utilization of a novel real-time intraoperative LFOVGC imaging approach can provide confirmation of MIBI-avid parathyroid adenoma removal appreciably faster than IOPTH and/or path and may provide a valuable adjunct to parathyroid surgery.